Spontaneous splenic rupture in infectious mononucleosis: a review. - Asgari, M. M. (Yale Journal of Biology and Medicine, 1997)
Spontaneous rupture of the spleen is a rare complication of infectious mononucleosis (IM) occurring in 0.1-0.5 percent of patients with proven IM [1]. Although splenectomy has been advocated as the definitive therapy in the past, numerous recent reports have documented favorable outcomes with non-operative management. A review of the literature suggests that non-operative management can be successful if appropriate criteria, such as hemodynamic stability and transfusion requirements are applied in patient selection. We report the case of a 36 year old man with infectious mononucleosis who had a spontaneous splenic rupture and who was successfully managed by splenectomy. Based on review of the literature, an approach to management of a spontaneously ruptured spleen secondary to IM is suggested.